Disparities in Regular Source of Dental Care among Mothers of Medicaid-Enrolled Preschool Children - Grembowski, David (2007)
For mothers of Medicaid children aged 3 to 6 years, we examined whether mothers’ characteristics and local supply of dentists and public dental clinics are associated with having a regular source of dental care. Disproportionate stratified sampling by racial/ethnic group selected 11,305 children aged 3 to 6 in Medicaid in Washington state. Mothers (N=4,373) completed a mixed-mode survey that was combined with dental supply measures. Results reveal 38% of mothers had a regular dental place and 27% had a regular dentist. Dental insurance, greater education, income, and length of residence and better mental health were associated with having a regular place or dentist for Black, Hispanic and White mothers, along with increased supply of private dentists and safety net clinics for White and Hispanic mothers. Mothers lacking a regular source of dental care may increase oral health disparities in their children.